DCUN1D1 promotes tumor progress in prostate cancer and its effect on DU145 in vitro - Shun-tan Huang; Ze-zhen Liu; Fu-Neng Jiang; Hui-chan He; Wei-De Zhong (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the expression levels of Defective In Cullin Neddylation 1 Domain Containing 1 oncogene in prostate cancer tissues and normal prostate tissues, to explored its effect on cancerous cells, and to investigate its underlying mechanisms on such cells in vitro. Methods: The cross-sectional study was conducted at Guangdong Key Laboratory of Clinical Molecular Medicine and Diagnostics from Jan 03,2017 to Nov 05,2018, and comprised prostate tissue samples on which immunohistochemistry was used to detect the expression of Defective In Cullin Neddylation 1 Domain Containing 1 oncogene. Short hairpin ribonucleic acid expression plasmid targeting the oncogene was constructed and transferred into prostate cance cell line DU145. The roles of the oncogene in prostate cancer progression were confirmed in vitro. The expression of vimentin and epithelial cadherin influenced by the oncogene were detected using Western blot. Data was analysed using SPSS 24. Results: Of the 80 samples, 3(3.75%) were normal prostate tissues, 7(8.75%) adjacent normal prostate tissues, 20(25%) hyperplasia, and 50(62.5%) prostate cancer tissues. Defective In Cullin Neddylation 1 Domain Containing 1 oncogene expression in prostate cancerous tissues was significantly associated with high Gleason score (p<0.001), metastasis (p<0.05) and pathological stage (p<0.001). The oncogene was found to be an independent prognostic factor for disease-free survival of prostate cancer patients (p=0.0108). In vitro analysis confirmed the tumour promotive role of the oncogene through cell proliferation, invasion and migration assays. Continuous...